2016
DOI: 10.1177/1741143216665841
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, absenteeism acceptance, and ethical climate as predictors of teachers’ absence and citizenship behaviors

Abstract: The goal of this study was to explore the mediating role of ‘absenteeism acceptance’ between different leadership styles and school ethical climate (SEC) on organizational citizenship behaviors (OCB) and voluntary absence among Israeli teachers. 304 teachers were randomly selected from 304 different mainstream and special-education schools. The model was analyzed using AMOS 18.0 software. We found that ‘absenteeism acceptance’ partially mediated the relationship between transactional leadership, SEC and OCB, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
3
30
1
4
Order By: Relevance
“…Job satisfaction and organizational commitment have been regularly studied as factors which affect and get affected by teacher OCB (Lapierre & Hackett, 2007; Sesen & Basim, 2012; Zeinabadi, 2010). Besides satisfaction and commitment, contextual factors including task characteristics, organizational characteristics and leadership behaviours have also been identified as antecedents of OCB among teachers (Elstad et al, 2011; Shapira-lishchinsky & Raftar-Ozery, 2016). Organizational identification has been emphasized as an important factor in determining OCB in schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Job satisfaction and organizational commitment have been regularly studied as factors which affect and get affected by teacher OCB (Lapierre & Hackett, 2007; Sesen & Basim, 2012; Zeinabadi, 2010). Besides satisfaction and commitment, contextual factors including task characteristics, organizational characteristics and leadership behaviours have also been identified as antecedents of OCB among teachers (Elstad et al, 2011; Shapira-lishchinsky & Raftar-Ozery, 2016). Organizational identification has been emphasized as an important factor in determining OCB in schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EC is the common understanding of various activities and ethical procedures, which also contains an ethical content [9]. The EC is reflected in organizational policies, and is associated with ethical consequences [10]. The EC determines the ethical values and behavior of the organization that influence the ethics of employees.…”
Section: Introductionmentioning
confidence: 99%
“…Blasé and Blasé (2002; 2003) found that when principals are abusive towards teachers, it can result in negative emotional, psychological, or physical responses, and affect teachers’ work in the classroom. Principals can also influence teacher absenteeism (Shapira-Lishchinsky and Raftar-Ozery, 2018) and their intent to leave (Shapira-Lishchinsky and Rosenblatt, 2009). Despite these outcomes, there is still little research on unethical leadership and its influence on the school.…”
Section: Introductionmentioning
confidence: 99%